2021
DOI: 10.1002/ags3.12520
|View full text |Cite
|
Sign up to set email alerts
|

Current status of perioperative nutritional intervention and exercise in gastric cancer surgery: A review

Abstract: Although it is steadily declining in incidence, gastric cancer remains one of the most common and deadly neoplasms worldwide. 1 Gastrectomy with sufficient lymph node dissection is recommended for patients with gastric cancer in whom endoscopic resection is not indicated. 2 However, gastric cancer surgery may be associated with several complications. Recent studies have reported that postoperative surgical complications affect the long-term oncological outcomes of gastric cancer. [3][4][5] Therefore, it is nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Trials of nutritional and exercise-based interventions, in isolation, for patients undergoing resection of upper GI cancer have yielded inconsistent results [ 95 , 96 ]. As Fearon suggested over a decade ago; cachexia is a multi-factorial syndrome that likely requires a multimodal intervention [ 97 ].…”
Section: Treat the Tumour And Treat The Hostmentioning
confidence: 99%
“…Trials of nutritional and exercise-based interventions, in isolation, for patients undergoing resection of upper GI cancer have yielded inconsistent results [ 95 , 96 ]. As Fearon suggested over a decade ago; cachexia is a multi-factorial syndrome that likely requires a multimodal intervention [ 97 ].…”
Section: Treat the Tumour And Treat The Hostmentioning
confidence: 99%
“…Surgical field complications such as leakage, pancreatic fistula, and abscesses had similar rates between the two groups. This was possibly attributable to the development of new devices [30, 31] and advanced perioperative management in Japan in recent decades [32, 33]. However, major grade 3 CD complications (and more) tended to be more frequent in the low CXI group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low CXI may need intensive nutritional and exercise guidance to improve skeletal muscle mass and prevent malnutrition before surgery. Although nutritional interventions has been less effective in the presence of malnutrition, loss of muscle mass, or sarcopenia with high inflammatory cytokines, 26 combination of nutritional and physical intervention may have possibility to improve these status compared with nutritional or physical intervention alone 27 . A study indicated that among sarcopenia patients with gastric cancer, 18% of those patients was improved to be nonsarcopenic after 3 weeks of preoperative exercise and nutritional support 28 .…”
Section: Discussionmentioning
confidence: 99%
“…with high inflammatory cytokines, 26 combination of nutritional and physical intervention may have possibility to improve these status compared with nutritional or physical intervention alone. 27 A study indicated that among sarcopenia patients with gastric cancer, 18% of those patients was improved to be nonsarcopenic after 3 weeks of preoperative exercise and nutritional support. 28 Moreover, another study showed that preoperative nutrition and exercise intervention in patients with gastric cancer have improved NLR, resulting in decreased secretion of cytokines and chemokines, which play important roles in cancer progression.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%